2006
DOI: 10.1038/nprot.2006.27
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the fast chromatin immunoprecipitation (ChIP) method

Abstract: Chromatin and transcriptional processes are among the most intensively studied fields of biology today. The introduction of chromatin immunoprecipitations (ChIP) represents a major advancement in this area. This powerful method allows researchers to probe specific protein-DNA interactions in vivo and to estimate the density of proteins at specific sites genome-wide. We have introduced several improvements to the traditional ChIP assay, which simplify the procedure, greatly reducing the time and labor required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
571
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 702 publications
(573 citation statements)
references
References 28 publications
2
571
0
Order By: Relevance
“…Here we tested an extraction buffer containing 150 mmol L 1 NaCl, 0.1% Triton X-100, and protease inhibitor cocktail. This buffer also provides a more stringent environment for protein-protein interactions, which will increase the antibody binding specificity and signal-to-noise ratio in downstream experiments like native chromatin immunoprecipitation (N-ChIP) (Nelson et al, 2006). Our result showed that the extraction buffer produced a dramatic increase in the yield of mono-nucleosomes, and even more so, di-nucleosomes ( Figure 3D).…”
Section: Optimization Of Mnase Digestion For Macsupporting
confidence: 49%
“…Here we tested an extraction buffer containing 150 mmol L 1 NaCl, 0.1% Triton X-100, and protease inhibitor cocktail. This buffer also provides a more stringent environment for protein-protein interactions, which will increase the antibody binding specificity and signal-to-noise ratio in downstream experiments like native chromatin immunoprecipitation (N-ChIP) (Nelson et al, 2006). Our result showed that the extraction buffer produced a dramatic increase in the yield of mono-nucleosomes, and even more so, di-nucleosomes ( Figure 3D).…”
Section: Optimization Of Mnase Digestion For Macsupporting
confidence: 49%
“…Chromatin Immunoprecipitation (ChIP) Assay-ChIP assay was performed as described previously (22). Anti-NF-YA or normal mouse IgG (Santa Cruz Biotechnology) antibodies were used in immunoprecipitation experiments.…”
Section: Establishment Of Tumors and Dna Delivery-n-[1-(23-dio-mentioning
confidence: 99%
“…ChIP analysis of in vivo binding of p53 to target promoters was performed as described (Nelson et al 2006). Briefly, cells were fixed with 1.42% formaldehyde for 15 min at room temperature, then neutralized with 125 mM glycine for 5 min.…”
Section: Subcellular Fractionationmentioning
confidence: 99%